The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1600-0765.2005.00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Variance components of gingival thickness

Abstract: Gingival thickness is mainly associated with tooth-related variables. Bleeding tendency is higher if gingiva is thin. Subject variability related to periodontal phenotype may add to the total variance, however, to a very low extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 28 publications
1
75
0
1
Order By: Relevance
“…5 In the present study the periodontal probing depth was associated with thicker gingiva among the cases, which was in accordance with observations made by several other authors who also reported that subjects with a thick periodontal phenotype had on an average higher mean periodontal probing depth. 19,20,21 However, such a correlation between the probing depth and gingival thickness did not exist in the control group.…”
Section: Discussionmentioning
confidence: 84%
“…5 In the present study the periodontal probing depth was associated with thicker gingiva among the cases, which was in accordance with observations made by several other authors who also reported that subjects with a thick periodontal phenotype had on an average higher mean periodontal probing depth. 19,20,21 However, such a correlation between the probing depth and gingival thickness did not exist in the control group.…”
Section: Discussionmentioning
confidence: 84%
“…This intraoral probe can measure the biological width and define the periodontal biotype, i.e. the thin and thick nature of the gums, which is a significant predictor of the periodontal outcome [39].…”
Section: Discussionmentioning
confidence: 99%
“…Transgingival probing method, which is a direct invasive measurement involving a periodontal probe, may be influenced by the diameter, angulation, and pressure of the periodontal probe and may cause the distortion of the tissue on probing; it is, however, simple and relatively inexpensive 3,10) . The ultrasonic method is also simple; however, the area available for study is limited by the large diameter of the probe and the results may be influenced by humidity 11,12,16,17) . Recently, many studies using radiographic measurements with CBCT have been reported.…”
Section: Discussionmentioning
confidence: 99%